Pengaruh Kualitas Layanan costumer knowledge dan lokasi terhadap nasabah tabungan Wadiah pada PT. LKMS BMT Almabruk Batusangkar - Wilda Yanti (Al-Hijrah: Journal of Islamic Economics And Banking, 2025)
This research is a field research with a quantitative approach. The population in this study were 257 customers of PT. LKMS BMT Almabruk Batusangkar with a sample of 72 people. The data collection technique used questionnaires and surveys. The data analysis used was quantitative data analysis which means using numbers to analyze the data. The data obtained will be processed using SPSS version 22. The results of the study are that Customer Knowledge Service (X1) has a significant effect on Wadiah Savings Customers (Y) at PT. LKMS BMT Al-Mabruk Batusangkar. Customer Knowledge Service (X1) and Location (X2) have an effect on Wadiah Savings Customers (Y) at PT. LKMS Al-Mabruk Batusangkar. This is evidenced by the calculated F value of 23.543 with a significance of 0.000. This can be seen in the statistical table at a significance level of 0.05 with df 2 (number of variables - 1) = 1 and df 2 (n-k-1) or (72-3-1) = 68 with n being the number of data and k being the number of variables where the results obtained for the F table are 3.13. It can be concluded that the calculated F> F table (23,543> 3.13) and the significance <0.05, namely (0.00<0.05). This means that Customer Service Knowledge (X1) and Location (X2) together have an influence on Wadiah Savings Customers (Y).Services (X1) with Location (X2) together have an influence on Wadiah Savings Customers (Y).